ANALISIS PERBANDINGAN KUALITAS PRODUK DAN PENGALAMAN PENGGUNA MOTOR HONDA BEAT DAN SUZUKI NEX DI KECAMATAN MALALAYANG - Dionisius Jocom; S.L.H.V. Joyce Lapian; Mirah H. Rogi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to determine the differences in product quality and user experience between Honda Beat and Suzuki Nex motorcycles among the community in Malalayang District. The method used in this study is a descriptive-comparative quantitative method, which is an approach used to compare two research objects to determine whether or not there are significant differences. Data was collected through the distribution of questionnaires, with sampling techniques using purposive sampling aimed at the community in Malalayang District who are users of one of these motorcycles. The data obtained was then analyzed statistically using the Independent Sample t-Test. The results of the study showed that there were no significant differences in product quality between the Honda Beat and Suzuki Nex. Meanwhile, in terms of user experience, the results of the study showed that there were no significant differences between the Honda Beat and Suzuki Nex, so that both products were considered to have a relatively similar level of satisfaction by the community in Malalayang District.